Efficient Optimization of the Performance of Mn2+‐Doped Kesterite Solar Cell: Machine Learning Aided Synthesis of High Efficient Cu2(Mn, Zn)Sn(S, Se)4 Solar Cells. Issue 12 (13th September 2018) - Li, Xiuling; Hou, Zhufeng; Gao, Shoushuai; Zeng, Yu; Ao, Jianping; Zhou, Zhiqiang; Da, Bo; Liu, Wei; Sun, Yun; Zhang, Yi
Abstract : Isoelectronic cation substitution is a potential method to decrease the density of Cu‐Zn anti‐site defects in CZTSSe, thus improving the V OC and performance of CZTSSe solar cells. The proper doping concentration is determined traditionally by the trial and error approach, costing much time, and materials. How to shorten the time to find the proper doping concentration is a big challenge for the development of solar cells. Here, by utilizing the machine learning model, the authors carry out an adaptive design for predicting the optimal doping ratio of Mn 2+ ions in CZTSSe solar cells for improved solar cell efficiency. With the help of machine learning prediction, the authors rapidly and efficiently find the optimal doping ratio of Mn 2+ in CZTSSe solar cells to be 0.05, achieving a highest solar cell efficiency of 8.9% in experiment. Further experimental characterizations of Mn‐doped CZTSSe show that the defect in CZTSSe after Mn doping is changed from an anti‐site CuZn defect to V Cu defect. Our findings suggest that machine learning is a very powerful and efficient approach to aid the development of solar cell materials for its application in the photovoltaic field. Abstract : Machine learning determines the optimal doping content of Mn 2+ in CZTSSe films effectively and rapidly for the best solar cell efficiency. A CM0.05 Z0.95 TSSe solar cell with an efficiency of 8.93% is achieved in the experiment. The doped Mn 2+ decreases the CuZn defect and boosts the improvement of CZTSSe solar cells.